ZOMBIE MYTH IN ALL OF US ARE DEAD SERIES (2021) - Rahmawati Rahmawati; Atinia Hidayah (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
This article discusses the myth of zombies in South Korea and discusses the deconstruction of zombie characters in the All of Us Are Dead series. The source of data from this study is the All of Us Are Dead series by Lee Jae-kyoo, Chun Sung-il and Kim Nam-su, which is adapted from the webtoon story Now at Our School by Joo Dong-geun. The purpose of writing this study is to find out the zombie myth that exists in South Korea and provide references about zombies and how the myth was developed. The author uses the theory written by Jaques Derrida. It uses descriptive qualitative methods to analyze data and employs library research to collect the data needed in the thesis. The author used the subtitle series All of Us Are Dead. The result of this study is human inversion of human and zombie, myth of zombie that shown in this series and deconstruction of zombie myth on human emotion created between different thoughts about the zombies.